Association of Immunogenicity and Drug Exposure and the Importance of Target Engagement in ADA Development: A Clinical Case Study of Anti-SARS-CoV-2 Biotherapeutics - Susan C. Irvin; Samit Ganguly; Zhiqiang Wang; Zhongqing Will He; Marguerite Alejandro; Kaitlin Donohue; Chinnasamy Elango; Chris Gallo; Stephen Guttmann; Shawn Kalicharan; Kristina Kameron; James Laird; et al. (The AAPS Journal, 2025)
The administration of therapeutic proteins, such as monoclonal antibodies (mAbs) may result in the formation of anti-drug antibodies (ADA), but there is limited publicly available data for biotherapeutics with exogenous targets or with targets in low abundance systemically. ADAs can impact a biotherapeutic’s safety, efficacy, and pharmacokinetics, so evaluation of immunogenicity is required for all therapeutic proteins. This analysis sought to evaluate the immunogenicity of two mAbs against COVID-19, casirivimab (CAS) and imdevimab (IMD) administered as a cocktail (CAS + IMD), in multiple clinical trials across different participant populations to add knowledge about the immunogenicity risk of protein therapeutics against exogenous targets and the association between immunogenicity and drug exposure. Overall, the incidence of treatment-boosted and treatment-emergent ADAs and neutralizing antibodies in both disease treatment and prophylaxis settings were low (i.e., < 11%). Participants in these studies were followed for up to 225 days post-last dose. Over time, the incidence of treatment-emergent and treatment-boosted immunogenicity for each mAb increased, but the rates and titers remained low overall; when it developed, patients usually developed ADA to both mAbs. Frequency of administration, dose, and route of administration did not appear to impact rates of immunogenicity. Concentrations of CAS and IMD were similar between participants of different immunogenicity status, indicating immunogenicity of CAS and IMD had no impact on pharmacokinetics of these mAbs; there was also no observed impact on safety or efficacy. The data presented here may provide supportive information for assessing the immunogenicity risk of protein therapeutics with exogenous targets. Graphical Abstract

Lessons learned through participatory bird-window collision research on a university campus - Hannah C. Partridge; Rebekah Netzley; Alex Wright; Joseph Amodeo; Sophie Barnett; Ron Baron; Braden French; Dakota Arneson; Sara A. Gagné (Urban Ecosystems, 2025)
Bird populations face many threats worldwide, including collisions with anthropogenic structures such as buildings’ windows. Bird-window collisions are gaining attention, but research and mitigation often face barriers including collision surveying guidelines, funding availability, and retrofitting costs and approvals. Beginning in 2022, we conducted research about bird-window collisions on an urban university campus to engage students in research and inform the implementation of mitigation at the site(s) with the most collisions. To achieve these goals, we worked with undergraduate and graduate students, faculty, staff, administrators, and media personnel to monitor bird-window collisions, spread the word throughout the community, and advocate for retrofitting buildings. Research was incorporated into a course-based undergraduate research experience, several undergraduate directed studies, paid undergraduate research positions, and volunteer opportunities. By the end of 2024, bird-friendly window markers were installed on two buildings on campus. In this article, we present the collective reflections and lessons learned from university stakeholders involved in the project. We recommend that similar conservation projects on university campuses (1) maximize project flexibility and consider how to best support stakeholders; (2) build impact and momentum over time by engaging stakeholders in unique ways; and (3) leverage participants’ previous experiences and use a solution-focused approach to ensure that participation is motivating and rewarding. With our lessons learned, similar projects on other university campuses may be able to attain more success in student engagement, project outcomes, and ultimately, the implementation of bird-friendly practices.

Challenging the Standard Immunogenicity Assessment Approach: 1-Tiered ADA Testing Strategy in Clinical Trials - Ching-Ha Lai; Mu Chen; Sasha Fraser; Jessica Wang; Sean McAfee; Emma Speaks; Nicholas Simeone; Jacqueline Rodriguez; Colin Stefan; Lisa DeStefano; Chinnasamy Elango; Matthew D. Andisik; et al. (The AAPS Journal, 2024)

Urban vultures preferentially roost at sites surrounded by landscapes with fewer edges between forest and urban development and near water - Hannah C. Partridge; Sara A. Gagné (Urban Ecosystems, 2023)

Validating within-limb calibrated algorithm using a smartphone attached infrared thermal camera for detection of arthritis in children - Erin Balay-Dustrude; Nivrutti Bhide; Joshua Scheck; Erin Sullivan; Kevin Cain; Debosmita Biswas; Savannah C. Partridge; Yongdong Zhao (Journal of Thermal Biology, 2023)

Global phylogeography of hyperdiverse lanternfishes indicates sympatric speciation in the deep sea - Jennifer J. Freer; Rupert A. Collins; Geraint A. Tarling; Martin A. Collins; Julian C. Partridge; Martin J. Genner (Global Ecology and Biogeography, 2022)
Aim Lanternfishes (Myctophidae) are one of the most species‐rich families of mid‐water fishes. They inhabit the mesopelagic zone, where physical barriers to dispersal and gene flow are permeable. Thus, modes of speciation that rely exclusively on geographical separation are potentially of less importance than those that rely more prominently on evolution of assortative mating through divergent habitat use and/or sexual signals, including visual signals from bioluminescent light organs. Here we used phylogenetic, ecological and morphological data to investigate the roles of geography, habitat use and lateral photophores in lanternfish speciation. Location Global. Time period Data collected between 1950 and 2015. Major taxa studied Lanternfishes (Myctophidae). Methods Ecological niche models (ENMs) were developed for 167 species, enabling the community composition of 33 mesopelagic ecoregions to be determined. Sequence data for seven protein‐coding regions from 175 species were used to reconstruct a phylogenetic tree of Myctophidae. Age‐overlap correlation tests were conducted using this phylogeny with outputs from ENMs (pairwise geographical overlap and pairwise ecological niche overlap, n = 136), in addition to matrices of pairwise depth overlap ( n = 158) and photophore pattern dissimilarity ( n = 161). Results Communities assembled according to nine broad climatic regions, and recently diverged species pairs possessed greater geographical and ecological niche overlap than more distantly related species, indicating that sympatric or parapatric speciation might be dominant modes of divergence. Differences in photophore patterns increased with the relative age of speciation events, suggesting that photophore patterns are largely constrained by phylogeny. Main conclusions Based on this evidence, we suggest that large‐scale oceanographic features structure the diversity of lanternfish communities and that speciation within this family of deep‐water fishes might not have required geographical isolation.

Interference in a Neutralizing Antibody Assay for Odronextamab, a CD20xCD3 Bispecific mAb, from Prior Rituximab Therapy and Possible Mitigation Strategy - Susan C. Irvin; Amanda D’Orvilliers; Nicolin Bloch; Kayla Boccio; Jason Pennucci; Jurriaan Brouwer-Visser; Erica Ullman; Manoj Rajadhyaksha; Mohamed Hassanein; Terra Potocky; Albert Torri; Aynur Hermann; et al. (The AAPS Journal, 2022)
A cell-based assay was developed to detect neutralizing anti-drug antibodies (NAbs) against odronextamab, a CD20xCD3 bispecific monoclonal antibody (mAb) under investigation for treatment of CD20+ B cell malignancies. In this assay, odronextamab bridges between two cell types, CD20-expressing HEK293 cells and CD3-expressing Jurkat T cells that generate a luciferase signal upon CD3 clustering. Patient samples containing NAbs directed to either arm of the bispecific drug block the odronextamab bridge formation between the cell lines thus preventing the generation of the luciferase signal. We determined that other anti-CD20 therapeutics also block bridge formation, resulting in false-positive results. In patient samples from odronextamab clinical trials, approximately 30% of baseline samples had a strong false-positive NAb signal that correlated with the presence of prior rituximab (anti-CD20) therapy. We determined that rituximab interference can be minimized by the addition of anti-rituximab antibodies in the NAb assay. Understanding and mitigating the impact of prior biologic exposure is increasingly important for implementing a successful bioanalytical strategy to support clinical drug development, especially in the immuno-oncology field. Graphical Abstract Odronextamab neutralizing antibody assay, interference, and mitigation. A Design of the odronextamab neutralizing antibody (NAb) assay where anti-CD20xCD3 drug bridges between CD20-expressing HEK293 cells and Jurkat T cells expressing an NFAT response element and luciferase reporter. True NAb prevents odronextamab from bridging between target and effector cells, thus preventing the expression of luciferase. B Interference with odronextamab from other anti-CD20 therapeutic antibodies (e.g., rituximab) from prior disease treatment generates a false-positive NAb result. Assay interference can be mitigated with an anti-idiotypic antibody against the interfering therapy.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Quantifying fishing activity targeting subsea pipelines by commercial trap fishers - Todd Bond; Dianne L. McLean; Corey B. Wakefield; Julian C. Partridge; Jane Prince; David White; Dion K. Boddington; Stephen J. Newman (Reviews in Fish Biology and Fisheries, 2021)

Bioanalytical Challenges due to Prior Checkpoint Inhibitor Exposure: Interference and Mitigation in Drug Concentration and Immunogenicity Assays - Andrew F. Dengler; Rachel Weiss; Tiffany Truong; Susan C. Irvin; Nidhi Gadhia; Mohamed Hassanein; Camille Georgaros; Jessica-Ann Taylor; Anne Paccaly; Giane Sumner; Matthew D. Andisik; Albert Torri; et al. (The AAPS Journal, 2021)
Monoclonal antibodies (mAbs) are a leading class of biotherapeutics. In oncology, patients often fail on early lines of biologic therapy to a specific target. Some patients may then enroll in a new clinical trial with a mAb specific for the same target. Therefore, immunoassays designed to quantify the current mAb therapy or assess immunogenicity to the drug may be susceptible to cross-reactivity or interference with residual prior biologics. The impact of two approved anti-PD-1 mAbs, pembrolizumab and nivolumab, was tested in several immunoassays for cemiplimab, another approved anti-PD-1 mAb. The methods included a target-capture drug concentration assay, a bridging anti-drug antibody (ADA) assay and a competitive ligand-binding neutralizing antibody (NAb) assay. We also tested bioanalytical strategies to mitigate cross-reactivity or interference in these assays from other anti-PD-1 biologics. Both pembrolizumab and nivolumab cross-reacted in the cemiplimab drug concentration assay. This was mitigated by addition of antibodies specific to pembrolizumab or nivolumab. ADA specific for pembrolizumab and nivolumab did not interfere in the cemiplimab ADA assay. However, pembrolizumab and nivolumab generated a false-positive response in a target-capture NAb assay. Our results demonstrate that similar exogenous pre-existing anti-PD-1 mAbs (biotherapeutics) such as pembrolizumab and nivolumab are detected and accurately quantified in the cemiplimab drug concentration assay. However, once steady state is achieved for the new therapy, prior biologics would likely not be detected. Cross-reactivity and interference in immunoassays from previous treatment with class-specific biotherapeutic(s) pose significant bioanalytical challenges, especially in immuno-oncology. Graphical abstract

AAPS Perspective on the EURL Recommendation on the use of Non-Animal-Derived Antibodies - B. Gorovits; A. Hays; D. Jani; C. Jones; C. King; A. Lundequist; J. Mora; M. Partridge; D. Pathania; S. S. Ramaswamy; D. Rutwij; H. Shen; et al. (The AAPS Journal, 2021)

Volumetric analysis and morphological assessment of the ascending olfactory pathway in an elasmobranch and a teleost using diceCT - Victoria Camilieri-Asch; Jeremy A. Shaw; Kara E. Yopak; Lucille Chapuis; Julian C. Partridge; Shaun P. Collin (Brain Structure and Function, 2020)

Mystery pufferfish create elaborate circular nests at mesophotic depths in Australia - Todd Bond; Robert J. Mueller; Matthew J. Birt; Jane Prince; Karen Miller; Julian C. Partridge; Dianne L. McLean (Journal of Fish Biology, 2020)
In 2011, the enigma of “mystery circles,” small but complex underwater structures first observed by divers from southern Japan in 1995, was solved when a new species of pufferfish, white‐spotted pufferfish ( Torquigener albomaculosus Matsuura 2014), was identified as the responsible agent. To date these circles have been described only from Japan, where they are formed on a sandy seafloor in water depths less than 30 m. A survey of oil field infrastructure on the North West Shelf of Western Australia in 2018 using a remotely operated vehicle and hybrid autonomous underwater vehicle (HAUV) recorded a high‐resolution video and bathymetric data of 21 circular formations with similar features to those described in Japan. The circles display dimensions and morphology like those described from Japan, but were observed in water depths between 129 and 137 m. The HAUV also recorded high‐resolution photographs which captured a Torquigener sp. fish in the immediate vicinity of the circles. An additional circle and Torquigener sp. were observed in images collected by baited remote underwater stereo‐video in a nearby location in 129 m depth. These circles are the first to be found in Australia. The pufferfish species responsible cannot be identified from images collected . Such a discovery not only generates intrigue and wonder among scientists and the general public but also provides an insight into the reproductive behaviour and evolution of pufferfish globally.

Future Distribution of Suitable Habitat for Pelagic Sharks in Australia Under Climate Change Models - Charlotte A. Birkmanis; Jennifer J. Freer; Leigh W. Simmons; Julian C. Partridge; Ana M. M. Sequeira (Frontiers in Marine Science, 2020)

Letter to the Editor regarding Davis B, McDermott S, McCarter M, Ortaglia A. 2019. Population-based mortality data suggests remediation is modestly effective in two Montana Superfund counties. Environ. Geochem. Health - J. Griffin; B. Macgregor; N. Greene; C. R. Partridge; J. Bryson; R. A. Schoof (Environmental Geochemistry and Health, 2020)

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Observations on the retina and ‘optical fold’ of a mesopelagic sabretooth fish, Evermanella balbo - H.-J. Wagner; J. C. Partridge; R. H. Douglas (Cell and Tissue Research, 2019)

Microstructural evolution of silicate immiscible liquids in ferrobasalts - Victoria C. Honour; Marian B. Holness; Jamie L. Partridge; Bernard Charlier (Contributions to Mineralogy and Petrology, 2019)

Gaze stabilization in mantis shrimp in response to angled stimuli - Ilse M. Daly; Martin J. How; Julian C. Partridge; Nicholas W. Roberts (Journal of Comparative Physiology A, 2019)

Phototactic tails: Evolution and molecular basis of a novel sensory trait in sea snakes - Jenna M. Crowe‐Riddell; Bruno F. Simões; Julian C. Partridge; David M. Hunt; Steven Delean; Julian G. Schwerdt; James Breen; Alastair Ludington; David J. Gower; Kate L. Sanders (Molecular Ecology, 2019)
Dermal phototaxis has been reported in a few aquatic vertebrate lineages spanning fish, amphibians and reptiles. These taxa respond to light on the skin of their elongate hind‐bodies and tails by withdrawing under cover to avoid detection by predators. Here, we investigated tail phototaxis in sea snakes (Hydrophiinae), the only reptiles reported to exhibit this sensory behaviour. We conducted behavioural tests in 17 wild‐caught sea snakes of eight species by illuminating the dorsal surface of the tail and midbody skin using cold white, violet, blue, green and red light. Our results confirmed phototactic tail withdrawal in the previously studied Aipysurus laevis , revealed this trait for the first time in A. duboisii and A. tenuis , and suggested that tail photoreceptors have peak spectral sensitivities between blue and green light (457–514 nm). Based on these results, and an absence of photoresponses in five Aipysurus and Hydrophis species, we tentatively infer that tail phototaxis evolved in the ancestor of a clade of six Aipysurus species (comprising 10% of all sea snakes). Quantifying tail damage, we found that the probability of sustaining tail injuries was not influenced by tail phototactic ability in snakes. Gene profiling showed that transcriptomes of both tail skin and body skin lacked visual opsins but contained melanopsin ( opn4x ) in addition to key genes of the retinal regeneration and phototransduction cascades. This work suggests that a nonvisual photoreceptor (e.g., Gq rhabdomeric) signalling pathway underlies tail phototaxis, and provides candidate gene targets for future studies of this unusual sensory innovation in reptiles.

Predicting ecological responses in a changing ocean: the effects of future climate uncertainty - Jennifer J. Freer; Julian C. Partridge; Geraint A. Tarling; Martin A. Collins; Martin J. Genner (Marine Biology, 2018)

Evidence of paternal nutrient provisioning to embryos in broad‐nosed pipefish Syngnathus typhle - C. Kvarnemo; K. B. Mobley; C. Partridge; A. G. Jones; I. Ahnesjö (Journal of Fish Biology, 2011)
In two experiments, radioactively labelled nutrients (either 3 H‐labelled amino‐acid mixture or 14 C‐labelled glucose) were tube‐fed to brooding male Syngnathus typhle . Both nutrients were taken up by the males and radioactivity generally increased in the brood pouch tissue with time. Furthermore, a low but significant increase of 3 H‐labelled amino acids in embryos was found over the experimental interval (48 h), whereas in the 14 C‐glucose experiment the radioactivity was taken up by the embryos but did not increase over the experimental time (320 min). Uptake of radioisotopes per embryo did not differ with embryo size. A higher uptake mg −1 tissue of both 3 H‐labelled amino acids and 14 C‐labelled glucose was found in smaller embryos, possibly due to a higher relative metabolic rate or to a higher surface‐area‐to‐volume ratio compared to larger embryos. Uptake in embryos was not influenced by male size, embryonic developmental advancement or position in the brood pouch. It is concluded that brooding males provide amino acids, and probably also glucose, to the developing embryos in the brood pouch.

A comparison of the physiological consequences of head-loading and back-loading for African and European women - R. Lloyd; B. Parr; S. Davies; T. Partridge; C. Cooke (European Journal of Applied Physiology, 2010)

Biomarker and stable carbon isotope analyses of sedimentary organic matter from Lake Tswaing: evidence for deglacial wetness and early Holocene drought from South Africa - I. Kristen; H. Wilkes; A. Vieth; K.-G. Zink; B. Plessen; J. Thorpe; T. C. Partridge; H. Oberhänsli (Journal of Paleolimnology, 2010)

Light environment and mating behavior in Trinidadian guppies (Poecilia reticulata) - Gabrielle A. Archard; Innes C. Cuthill; Julian C. Partridge (Behavioral Ecology and Sociobiology, 2009)

Ultraviolet photopigment sensitivity and ocular media transmittance in gulls, with an evolutionary perspective - Olle Håstad; Julian C. Partridge; Anders Ödeen (Journal of Comparative Physiology A, 2009)

Soil and vegetation responses to hydrological manipulation in a partially drained polje fen in New Zealand - B. K. Sorrell; T. R. Partridge; B. R. Clarkson; R. J. Jackson; C. Chagué-Goff; J. Ekanayake; J. Payne; P. Gerbeaux; N. P. J. Grainger (Wetlands Ecology and Management, 2007)

Deep sea benthic bioluminescence at artificial food falls, 1,000–4,800 m depth, in the Porcupine Seabight and Abyssal Plain, North East Atlantic Ocean - E. J. V. Gillibrand; P. Bagley; A. Jamieson; P. J. Herring; J. C. Partridge; M. A. Collins; R. Milne; I. G. Priede (Marine Biology, 2007)

Effects of an Environmental Estrogen on Male Gulf Pipefish, Syngnathus scovelli (Evermann and Kendall), a Male Brooding Teleost - N. Ueda; C. Partridge; J. Bolland; J. Hemming; T. Sherman; A. Boettcher (Bulletin of Environmental Contamination and Toxicology, 2005)

Vision and visual variation in the peacock blenny - E. M. White; D. M. GonÇalves; J. C. Partridge; R. F. Oliveira (Journal of Fish Biology, 2004)
Microspectrophotometry (MSP) revealed the presence of a rod and at least two cone classes (mid‐ and long‐wavelength sensitive) in the intertidal peacock blenny Salaria pavo . Both rhodopsin and porphyropsin based visual pigments were found in all fish, together with high individual variation in the chromophore ratio. The three morphs (females, males and sneaker males) differed in their spectral sensitivities (as measured with the optomotor response) with sneakers having higher sensitivity at long‐wavelengths than either males or females. This long‐wave displacement of peak sensitivity could be due to elevated proportions of porphyropsin visual pigments in the sneakers’ retinae. The lenses of all morphs exhibited a short‐wavelength cut‐off and an unusual layer of carotenoid was found behind the retinal pigment epithelium and in the outer segments of some cones. These screening pigments could serve a photo‐protective role or to improve visual contrast. No short‐wave photoreceptors were located using MSP. This indicates that this cone class may be absent or present at very low numbers in the retina. This is the first in depth study of the visual system of a blenniid fish and indicates potential within‐species visual variation that may be related to the species’ habitat and morph‐specific behavioural requirements.

Sex differences in dogfish behaviour: alternative activity patterns and habitat choice - V. J. Wearmouth; D. W. Sims; J. C. Partridge; I. C. Cuthill (Journal of Fish Biology, 2003)
Acoustic tracking of wild lesser spotted dogfish, Scyliorhinus canicula , in Lough Hyne, a tidal sea‐water lough in southwest Ireland, has demonstrated that the sexes exhibit alternative behaviours. Male dogfish remain active throughout the day and night in deep water (12–24 m), and forage in shallow or deep water by night. Female dogfish, on the other hand, refuge in shallow water caves by day (

Avian colour vision and avian video playback experiments - I. C. Cuthill; N. S. Hart; J. C. Partridge; A. T. D. Bennett; S. Hunt; S. C. Church (acta ethologica, 2000)

Visual pigments, oil droplets, ocular media and cone photoreceptor distribution in two species of passerine bird: the blue tit ( Parus caeruleus L.) and the blackbird ( Turdus merula L.) - N. S. Hart; J. C. Partridge; I. C. Cuthill; A. T. D. Bennett (Journal of Comparative Physiology A, 2000)

The new hominid skeleton from Sterkfontein, South Africa: age and preliminary assessment - Timothy C. Partridge; John Shaw; David Heslop; Ronald J. Clarke (Journal of Quaternary Science, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Does Lepidopteran Larval Crypsis Extend into the Ultraviolet? - Stuart C. Church; Andrew T. D. Bennett; Innes C. Cuthill; Sarah Hunt; Nathan S. Hart; Julian C. Partridge (The Science of Nature, 1998)

On the visual pigments of deep‐sea fish - R. H. Douglas; J. C. Partridge (Journal of Fish Biology, 1997)
The retinal visual pigments of 52 species of deep‐sea fish were measured by partial bleaching of detergent extracts. The retinae of 45 species contained only a single rhodopsin with maximum absorbance (λ max ) at a wavelength between 474 and 490 nm, matching both the region of highest intensity downwelling sunlight and the maximum emission of most deep‐sea bioluminescence. Seven species were shown to have more than one visual pigment within their retinae and these had λ max values that generally fell outside the usual range. One of these, Bonapartia pedaliota , was particularly interesting as, unlike most such multipigment species, it had one rhodopsin and one porphyropsin pigment, apparently based on different opsins. The relative proportions of the visual pigments in the seven multipigment species are presented.

The effect of t-butylated hydroxytoluene on glutathione linked detoxification mechanisms in rat - Catherine A. Partridge; Dat D. Dao; Thomas D. Hong; Gopal Misra; Dean S. Folse; Yogesh C. Awasthi (Archives of Toxicology, 1983)